Nanostructured and hybrid engineering thin films - Sun, Yong. (2008)
The specific technical objectives are identified as follows: (1) To develop a magnetron sputtering system which can be employed to deposit multicomponents simultaneously to form nanostructured and hybrid films. (2) To design and fabricate nanocomposite and hybrid films based on the TiO2/conducting particles system to achieve effective EMI shielding for miniaturized electronic devices. (3) To develop superhard nanocomposite and hybrid films for tribological applications, based on doping of ceramics with rare earth elements and the proper combination of nitrides, borides, and silicides to nanocrystalline/amorphous composites. (4) To characterize the resultant nanostructured and hybrid films in terms of various structural and related properties features.